ANALISIS PENENTUAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE ACTIVITY BASED COSTING PADA UMKM TAHU BU KARNI - Shellya Agustina; Nur Endah Fajar Hidayah (Jurnal Akuntansi dan Bisnis, 2025)
This research is motivated by the importance of accuracy in determining production costs as a basis for setting selling prices and making managerial decisions, especially in small businesses that produce more than one product. The method used in this study is a qualitative descriptive method with a case study approach. Data were obtained through interviews, direct observation, and production cost documentation. COGS calculations were conducted for two types of products: white tofu and fried tofu, comparing the results between the MSME system and the ABC method. The results show that the traditional method yielded COGS of Rp 541.20 for white tofu and Rp 446.90 for fried tofu. Meanwhile, the ABC method resulted in COGS of Rp 524,60 for white tofu and Rp 441.70 for fried tofu. This calculation difference indicates cost distortion in the traditional method, with an overcosting of Rp 16,60 for white tofu and an overcosting of Rp 5,20 for fried tofu. The ABC method is more accurate because it allocates overhead costs based on the actual activity consumption of each product. Furthermore, the ABC method provides more relevant cost information for decision-making, particularly in determining selling prices and cost efficiency. Therefore, the ABC method is highly recommended for MSME] with diverse products with different production process characteristics